Investigating the Properties of Shrub Biomass Pellets Through Additive and Sawdust Admixing - Diaz, J (Elsevier Ltd, 2024)
This study investigated pellets produced using shrub biomass blended with pine sawdust to improve their physical and combustion properties by incorporating additives. First, the properties of pellets produced at different temperatures were analyzed. Pellets produced using pine sawdust blended with Teline monspessulana and Ulex europaeus biomasses (80/20 %m/m) exhibited good properties when prepared at 50–60 °C, whereas pellets produced using Rubus ulmifolius exhibited better characteristics at lower temperatures. The results showed that further studies on the physical properties and operational conditions of biomass from Ulex europaeus and Rubus ulmifolius are required. Furthermore, pellets blended with Teline monspessulana were evaluated using starch and lignin as binders, which exhibited all the physical properties of ISO 17225–6 when 1 wt% lignin was added owing to the stronger bonding induced by the additive. Because the fuel indices indicated a high corrosion risk, the additive CaO was used to improve the combustion performance of pellets blended with Teline monspessulana biomass and binders. The content of particulate matter smaller than 2.5 and 10 μm decreased by approximately 50%, and the crystallinity of the bottom ash, which usually contains undesirable elements, was improved by adding 1 wt% CaO, which raised the melting temperature of the ash. © 2024 Elsevier Ltd